The gut hormone, Glucagon-Like Peptide 2, contributes to the improved glycaemic control observed post-bariatric surgery, as a result of its intestinotrophic effects - Rudge, Eleanor J.M. (2020)
BACKGROUND Bariatric surgery, specifically Roux-en-Y Gastric Bypass (RYGB), leads to durable weight loss as well as significant improvements in Type 2 Diabetes (T2D). Despite multiple randomised studies showing superiority of RYGB to maximal medical therapy for treatment of T2D, surgery remains grossly underutilised with only 1-2% of patients who qualify for the surgery proceeding with it. The limited acceptance of surgery highlights the need for less invasive interventions that can replicate the metabolic success of RYGB. A better understanding of the anti-diabetic mechanisms of surgery is therefore required in order to allow the development of less invasive T2D therapies (e.g. less invasive surgery, a medical device, or medication) which can then be offered to a wider patient population. RYGB appears to exert its anti-diabetic effects through multiple mechanisms. Work previously carried out within this lab has suggested that, post-RYGB surgery, there is a decrease in intestinal glucose absorption, with an increase in intestinal glucose utilisation. This thesis seeks to gain corroborating data in order to further decipher glucose utilisation and absorption patterns post-RYGB surgery. Additionally, it aims to determine whether these glucose modulations could be linked to the intestinal hypertrophy observed post-RYGB, and whether it could be mediated by Glucagon-Like Peptide 2 (GLP-2), a potent intestinotrophic hormone found at higher concentrations following RYGB.